Efficient and Secure Access Control for IoT-based Environmental Monitoring - Aljahdali, Asia Othman; Habibullah, Afnan; Aljohani, Huda (Engineering, Technology & Applied Science Research, 2023)
Environmental monitoring devices based on IoT collect a large amount of data about the environment and our surroundings. These data are collected and processed before being uploaded to third-party servers and accessed and viewed by ordinary or specialized users. However, they may hold sensitive information that should not be exposed to unauthorized users. Therefore, accessing this sensitive information must be strictly controlled and limited in order to prevent unauthorized access. This research intends to create an access control mechanism based on distributed ledger technologies. The idea is to use a hybrid of IOTA technology and Ciphertext-Policy Attribute-Based Signcryption (CP-ABSC) technology. The permissions to access these data are written in a token, and this token will be sent to the Tangle after being signcrypted with CP-ABSC. Consequently, the data will be safeguarded, their confidentiality and integrity will be maintained, and unauthorized individuals will be unable to access the information. The proposed system was evaluated in terms of performance and the results showed that the system is straightforward, rapid, and convenient to use. Furthermore, a security assessment was conducted by running several scenarios to evaluate its feasibility and protection.